Implementación del sistema de control interno y su incidencia en el proceso de adquisiciones, Hospital Regional Docente de Trujillo – 2017 - Garay Meléndez, Erika Roxana (2020)
ABSTRACT The outdated and non-existent management documents, as well as the ignorance of the Internal Control System has caused the procurement processes to be carried out inefficiently in a public entity. The implementation of the Internal Control System is within the framework of Directive N ° 13-2016-CG / GPROD, which establishes the Comptroller's Office to put the Internal Control System into operation in state entities and describes the following phases of the Implementation: Planning, Execution and Evaluation, that is why the present research work will be applied in the first phase, which aims to propose the Implementation of the Internal Control System, to determine how it affects the improvement of the Procurement Process, Hospital Regional Teacher of Trujillo 2017, for which the methodology that corresponds to a non-experimental transversal research of explanatory descriptive type was used. The sample population was made up of 35 workers. The survey technique was applied and the instrument is the questionnaire that has been applied to workers in the area of procurement and administrative headquarters, as well as assistance. An interview with the headquarters of the Logistics Office was also included to measure their level of knowledge of the relevant regulations in the area that allow the corresponding decisions to be taken. From the result obtained, it was detected that the procurement process has deficiencies and irregularities when executed, identifying that no purchases are made, do not comply with the Annual Contracting Plan and are mostly unaware of the Contracting Law, so it is concluded that the implementation of the internal control system is of vital importance to improve the processes. In response to the deficiencies found, it is proposed to design a work plan in order to implement an adequate Internal Control System based on the components of internal control that are indispensable, since not only is it sought to measure risks but also to promote and optimize efficiency, effectiveness , transparency, economy in the operations of the Institution including the ethical values, integrity as well as the quality of the public services that it provides, to preserve the institutional patrimony, of losses due to waste, abuse, mismanagement, errors, frauds or irregularities and guarantee Optimal institutional management.